The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2176/nmc.52.234
|View full text |Cite
|
Sign up to set email alerts
|

Intradural Invasion of Lumbar Synovial Cyst

Abstract: A 63-year-old female presented with a rare case of synovial cyst invading the dura mater and mimicking an intradural extramedullary tumor in the lumbar spine. She underwent posterior lumbar fusion with laminar wire fixation from L3 to S1 levels. She complained of severe pain along the anterolateral thigh in both legs for 1 year. Radiological examinations, including magnetic resonance imaging and computed tomography revealed an intradural extramedullary lesion at the L2-3 level that was compressing the thecal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…23,24 However, juxtafacet cysts can arise anywhere adjacent to the facet joints, and cause intra-or extraforaminal nerve compression; 24,40,43,64,92 even intradural cysts have been reported. 9,89 Just as disc herniation can occur far lateral to the foramen, 58 synovial cysts can cause far-lateral nerve impairment as well. 56,74 Interestingly, in a radiological survey of patients with symptomatic lumbar cysts, Doyle and Merrilees 21 observed 3 times more cysts posterior, and therefore outside the spinal canal, than anterior to the facet joint.…”
Section: Location Of Cystmentioning
confidence: 99%
“…23,24 However, juxtafacet cysts can arise anywhere adjacent to the facet joints, and cause intra-or extraforaminal nerve compression; 24,40,43,64,92 even intradural cysts have been reported. 9,89 Just as disc herniation can occur far lateral to the foramen, 58 synovial cysts can cause far-lateral nerve impairment as well. 56,74 Interestingly, in a radiological survey of patients with symptomatic lumbar cysts, Doyle and Merrilees 21 observed 3 times more cysts posterior, and therefore outside the spinal canal, than anterior to the facet joint.…”
Section: Location Of Cystmentioning
confidence: 99%
“…Several case reports have been published on "intradural synovial cysts" (IDSCs). [8][9][10][11][12][13][14][15][16][17][18][19] A review of these reports showed that dural penetration of the extradural cyst most frequently occurs at the craniovertebral junction. Neurological symptoms had been caused by direct compression of the spinal cord, brain stem, or hypoglossal nerve.…”
Section: Introductionmentioning
confidence: 99%
“…4,10 However, there are reports of spontaneous regression of such cysts, 7,11 as well as intradural invasion 12 or spontaneous hemorrhage causing a cauda equina syndrome or bilateral foot drop. 13,14 The clinical symptoms can differ and are difficult to predict.…”
Section: Introductionmentioning
confidence: 99%
“…There are reports of spontaneous cyst regression as well as regression after anti-inflammatory drug treatment with Cox-2 inhibitors. 7,12 There are also reports showing that cysts can lead to cauda equina syndrome and have deleterious outcomes for patients. 7 There is no need to treat asymptomatic cysts and a conservative treatment can be applied in symptomatic small cysts without neurological deficits in our opinion.…”
Section: Introductionmentioning
confidence: 99%